The Poet and the Architect: a Consideration on Byzantine Epigrams - Avagliano, Alessandra (Actual Problems of Theory and History of Art, 2013)
In Byzantium, since the earlier centuries, it was common to use long dedicatory inscriptions carved on buildings. Th ese texts were tightly linked to the building they were sculpted on, being a part of the decoration itself. It is necessary to analyze the epigrams themselves and their connection with the Byzantine architecture and society, in which they were written. A comparative analysis of texts, architecture and culture milieu can provide new stimulus for refl ection.